The Role of Halal Labels in Influencing Brand Image, Product Quality, and Purchase Decisions of Scarlett Whitening Skincare Products - Irtikha , Fianti; Nora , Liza (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
The rapid development of the beauty industry in Indonesia encourages companies to increase competitiveness through effective marketing strategies. This study aims to analyze the effect of brand image and product quality on purchasing decisions for scarlett whitening in the jabodetabek area, as well as the role of the halal label as a moderating variable. The method used is quantitative research with the structural equation modeling partial least square (SEM-PLS) approach using SmartPLS software. Data were obtained through distributing questionnaires to scarlett whitening consumers in Jabodetabek using a Likert scale as a measuring tool. The results showed that brand image and product quality have a positive and significant effect on purchasing decisions. In addition, the halal label is proven to significantly moderate the effect of brand image on purchasing decisions, and the halal label does not significantly affect product quality on purchasing decisions. These findings emphasize the importance of building a strong brand image, maintaining product quality, and paying attention to halal aspects of products to increase consumer loyalty and purchasing decisions, especially among Muslim consumers.